Improving Employee Performance Through the Role of Employee Trust by Considering Employee Engagement and Organizational Culture - Hartono, Rahmad; Soerjanto, Soerjanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study set out to ascertain the relationship between employee trust as an intervening variable and the effects of organizational culture and employee engagement on employee performance. This research uses quantitative methods, namely by analyzing the Least Squares Technique (PLS). There were 120 participants in the study's sample. Saturated sampling was used to get primary data via questionnaires. Path analysis, direct effect, and indirect effect are among the data that are collected through the use of questionnaires and hypothesis testing. The findings demonstrated that while organizational culture and employee engagement had no direct impact on performance, they did have a favorable and considerable impact on employee trust. Employee performance is also positively and significantly impacted by employee trust. Employee engagement and organizational culture have a positive and significant effect on employee performance through employee trust. The relationship between employee engagement, company culture, and employee performance is mediated by the variable of trust. The results of this study can provide practical guidance for management and HRD in designing policies and programs aimed at improving employee performance through the development of trust, engagement, and a healthy organizational culture.